FACTORS AFFECTING THE INCIDENCE OF ISPA TO TODDLERS IN THE BENDAN HEALTH CENTER WORKING AREA - Rahmatika, Shilnia; Mastuti, Dewi Nugrahaeni Restu; Maulana, Jaya; Falla, Aisya Nurul; Aini, Fadhilla Anisa Nur; Azmi, Zubaidah Tsania Ulul (PT. Hafasy Dwi Nawasena, 2025)
According to the World Health Organization (2023), there are 13 million deaths from acute respiratory infections (ARI) each year, with 4 million occurring in Indonesia. The goal is to reduce ARI deaths by 25% from 2021-2022 and achieve a 10% reduction in mortality over the next seven years. In Indonesia, 4.8% of children under five are diagnosed with ARI, particularly in densely populated areas like Central Java. Factors such as humidity, smoking habits, and maternal education contribute to the risk of ARI in young children. To study these risk factors in Kelurahan Bendan Kergon, analytic quantitative research was conducted in November-December 2024. The population consisted of 870 toddlers aged 1-5 years, with 100 samples selected using the slovin technique. The study used a cross-sectional design with purposive sampling and measured variables using hygrometer and lux meter instruments. Statistical Package for the Social Sciences (SPSS) was used for data analysis, which revealed that some variables, such as knowledge, smoking behavior, and humidity, were not associated with the incidence of ARI. However, lighting level was found to be a significant variable.